Applications‎ ~‎of $Q$-hypergeometric and Hurwitz‎-Lerch Zeta Functions on Meromorphic Functions - Seyed Hadi Sayedain Boroujeni; Shahram Najafzadeh (Mathematics Interdisciplinary Research, 2023)
‎A new subclass of meromorphic univalent functions by using the q-hypergeometric and Hurwitz-Lerch Zeta functions is defined‎. ‎Also‎, ‎by applying the generalized Liu-Srivastava operator on meromorphic functions‎, ‎some geometric properties of the new defined subclass such as coefficient estimates‎, ‎extreme points‎, ‎convexity and connected set structure are investigated‎.